Speculating About Robot Moral Standing: On the Constitution of Social Robots as Objects of Governance - De Pagter, Jesse (Frontiers in Robotics and AI, 2021)
In recent years, the governance of robotic technologies has become an important topic in policy-making contexts. The many potential applications and roles of robots in combination with steady advances in their uptake within society are expected to cause various unprecedented issues, which in many cases will increase the demand for new policy measures. One of the major issues is the way in which societies will address potential changes in the moral and legal status of autonomous social robots. Robot standing is an important concept that aims to understand and elaborate on such changes in robots’ status. This paper explores the concept of robot standing as a useful idea that can assist in the anticipatory governance of social robots. However, at the same time, the concept necessarily involves forms of speculative thinking, as it is anticipating a future that has not yet fully arrived. This paper elaborates on how such speculative engagement with the potential of technology represents an important point of discussion in the critical study of technology more generally. The paper then situates social robotics in the context of anticipatory technology governance by emphasizing the idea that robots are currently in the process of becoming constituted as objects of governance. Subsequently, it explains how specifically a speculative concept like robot standing can be of value in this process.